Aracaju sob rodas : aspectos da mobilidade urbana no viés do transporte público - Vasconcelos, Alana Danielly (2014)
Today´s society is facing many challenges, of which the biggest one is to continue to be globalized and at the same time sustainable. Thus, the search for alternatives to them, requires a never before experienced effort. The rapid expansion of cities in Brazil, put issues such as urban mobility on the agenda for discussion, raising problems such as traffic jams, traffic deaths, lack of infrastructure of roads, lack of security, insecurity in public transport that make locomotion unsafe act and stressful for the citizen. The public roads remain the same, the number of private cars grows in the streets and no brakes. Given the above and taking public transport as an outlet for mitigation of problems in the context of mobility is that this study evaluated the urban mobility in the city of Aracaju, Sergipe, with regard to service and people´s access to the city´s public transport system through desk research, field and observational. The results of this study show that there must be a change in thinking of the general population. Need to understand that there is not a privilege but a right to move safely and comfortably within a city for all who compose it. Traffic routes are public goods and should be distributed according to the amount of people, not vehicles. The city should be designed for pedestrians, not for cars. The public transport has priority on the roads, then, allows the mass transport of the population. This should give security and comfort to its users. Thus, urban planning built together, demonstrates the people a service with transparency, accountability and the existence of a management based on democracy. It is hoped therefore that this research will be useful in the sphere of planning and management of the municipal territory, contributing as a monitoring tool of urban mobility, seeking to present paths to sustainable urban development of the city of Aracaju.